Difficulties of the customer-supplier relationship at small enterprises - Morauszki, Kinga Szilvia (Studia Mundi – Economica, 2019)
It is vital for customers to build coordinated and cooperative long-term relationships with other companies. According to Mohr and Spekman (1994) a partnership is such an intended relationship of strategic importance between two independent companies which have shared goals, strive for mutual benefits and there is strong interdependence between them. Like in any relationship, there are difficulties, problems, and conflicts in the relationship between the members of the supplier chain, as the parties try to promote their interests. In the course of this process, there might be disagreement, difficulties and problems, which should not be ignored, and some kind of a solution must be found. In this study, we deal with the problems of small enterprises.
Keywords: difficulty; problem; small enterprises; supplier; relationship